The Effectiveness of the Simulation Training-Based Clinical Base Learning Model on The Safety Competence of Nursing Students in Hospitals - Irwan Hadi; Hapipah Hapipah; Aswati Aswati; Baiq Nurainun Apriani Idris (Indonesian Journal of Global Health Research, 2025)
Patient safety is a fundamental aspect of nursing practice that must be instilled from the time of education. However, many nursing students do not have adequate competence in applying the principles of patient safety during clinical practice. A Simulation Training-based Clinical Base Learning Model (CBL-ST) was developed to answer these challenges. This study uses a mixed methods approach with a sequential explanatory design. The first stage was carried out qualitative exploration through in-depth interviews with 10 clinical supervisors to prepare the CBL-ST intervention module. The second stage used a quasi experiment design. Sample with purposive sampling with the criteria of a student with a minimum of semester 5, have participated in clinical practice and are willing to be respondents as  80 nursing students, divided into intervention and control groups. Patient safety competency was measured using the Patient Safety Attitude (PSA) instrument, analyzed by the t-test. Results showed a significant improvement in scores in the intervention group (pretest 68.5; posttest 85.3; p < 0.05) compared to the control group (pretest 67.9; posttest 70.1; p > 0.05). The five key themes of the qualitative outcomes include: patient-centered service, patient safety goals, teamwork, effective communication, and safety culture. The CBL-ST model is proven to not only improve cognitive and technical aspects, but also shape professional values and student safety culture. The CBL-ST model is effective in significantly improving the safety competence of nursing student patients. The application of case-based simulation learning can be a systematic clinical education strategy that has a long-term impact on the quality of health services.